(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2022)
The best practices model is one of the most prominent models of process re-engineering as an integrated work system based on describing the current situation as it is, then evaluating the current situation, and proposing future operations, as process re-engineering seeks to improve radically, not just continuous improvement and serves as an entry point for reform administration in general. The Syrian banking sector in general suffers from a decline in the level of quality of banking service it provides to clients. The research aims to evaluate the role of the best practices model in addressing the problems of low quality of banking services by applying to Syrian private banks, in particular with regard to electronic banking services that private banks have put into the market, and whose launch resulted in the reengineering of banking operations in line with the requirements for providing these services. To achieve this, two main hypotheses were formulated, and the researcher used the questionnaire method to collect the data that was analyzed using statistical tests, the most important of which are: The One-Sample T. test, the Pearson Correlation test, and regression analysis. The researcher reached several results, the most important of which are: A strong direct relationship between the application of the best practices model and the quality of banking service in the private banks under study.